Insomnia in seasonal affective disorder: considering the use of benzodiazepines with a focus on lormetazepam - Biggio, Giovanni; Mencacci, Claudio (Frontiers in Psychiatry, 2026)
BackgroundSeasonal affective disorder (SAD) occurs in two main forms: winter-pattern SAD, associated with depressive symptoms during shorter, darker days; and summer-pattern SAD, linked to mood disturbances during longer, hotter days. SAD may develop into a chronic condition with recurring depressive episodes. Risk factors for SAD include geographic latitude, age, gender, genetic predisposition, and lifestyle. Sleep disturbances, such as insomnia, hypersomnia, and circadian rhythm disruptions, are common and can amplify emotional symptoms.ObjectiveThis review explores the clinical features and management strategies for insomnia associated with SAD, focusing on the potential of benzodiazepines (BZDs), in particular lormetazepam.ResultsControversies surround current nonpharmacological and pharmacological strategies for managing sleep disorders in SAD. This review emphasizes the importance of using more effective treatments for insomnia associated with SAD, currently an unmet need. In particular, clinical evidence supports the potential benefits of intermittent hypnotic BZDs to treat insomnia. Among the BZDs, short-term or intermittent use of lormetazepam is an effective treatment option in the management of insomnia.ConclusionInsomnia associated with SAD is an important symptom to monitor because it impacts the patient’s quality of life. BZDs, including lormetazepam, are a standard short-treatment option for insomnia that could improve the sleep symptoms associated with SAD. Comparative clinical trials of the efficacy and safety of lormetazepam in this patient population are required to confirm this.